Continuous Positive Airway Pressure versus Mechanical Ventilation on the First Day of Life in Very Low-Birth-Weight Infants - Flannery, Dustin D.; O'Donnell, Elizabeth; Kornhauser, Mike; Dysart, Kevin; Greenspan, Jay; Aghai, Zubair H. (American Journal of Perinatology, 2016)
Objective The objective of this study was to determine differences in the incidence of bronchopulmonary dysplasia (BPD) or death in very low-birth-weight (VLBW) infants managed successfully on continuous positive airway pressure (CPAP) versus mechanical ventilation on the first day of life (DOL).Study Design This is a retrospective analysis of the Alere neonatal database for infants born between January 2009 and December 2014, weighing ≤ 1,500 g. Baseline demographics, clinical characteristics, and outcomes were compared between the two groups. Multivariable regression analysis was performed to control the variables that differ in bivariate analysis.Results In this study, 4,629 infants (birth weight 1,034 ± 290 g, gestational age 28.1 ± 2.5 weeks) met the inclusion criteria. The successful use of early CPAP was associated with a significant reduction in BPD or death (p < 0.001), as well as days to room air, decreased oxygen use at discharge, lower risk for severe intraventricular hemorrhage, and patent ductus arteriosus requiring surgical ligation (p < 0.001 for all outcomes).Conclusion Successful use of early CPAP on the first DOL in VLBW infants is associated with a reduced risk of BPD or death.
Keywords: continuous positive airway pressure; prematurity; bronchopulmonary dysplasia; very low birth weight